Implementasi Nilai-Nilai Pancasila dalam Era Digital - Tasya Salsabilah Efendi; Nazwa Dwi Savitri; Azenia Lisani Putri; Dinda Puspita Sari; Rafli Annaufal; Yoan Abdul Ghani (JURNAL RISET MANAJEMEN (JURMA), 2025)
Pancasila, as the foundation of the Indonesian state, plays a fundamental role in social and national life. However, the advancement of the digital era presents new challenges in upholding the values of Pancasila, such as the spread of hoaxes, hate speech, and radicalization through social media. This article aims to analyze the application of Pancasila values in facing social changes influenced by the advancements of digital technology. The research uses a library research method by analyzing various literatures related to Pancasila and the impact of the digital era on social life. The research findings indicate that although digital technology offers convenience in disseminating information, significant challenges arise in the form of individualism, materialism, and the misuse of social media, which can threaten national unity. Therefore, it is essential to strengthen public understanding of Pancasila values through proper digital literacy and introduce cultural education to maintain social harmony. Additionally, regulations supporting ethics and norms in the digital world are crucial to prevent the negative impacts of technological misuse. Pancasila must remain relevant amidst technological progress, by making it a guide in daily life to preserve national unity in facing the challenges of the digital era.